2008
DOI: 10.1111/j.1600-0463.2008.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of non‐mast cell histidine decarboxylase in tumor‐associated microvessels in human esophageal squamous cell carcinomas

Abstract: Histamine is produced by mast cells and many other types of cells. The role of histamine released from mast cells in promoting tumor angiogenesis has been intensively studied; however, the role of non-mast cell histamine in regulating tumor angiogenesis has been largely ignored. In this study, tissue specimen sections from 43 patients with esophageal squamous cell carcinoma (ESCC) and normal esophageal biopsies from 17 heath individuals obtained from a high incidence area of north China were used to assess cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Also, Elpek et al (2001) have reported that CD34+-positive intra-tumoural microvessel density was associated with poorer survival in oesophageal squamous cell cancer. Finally, consistent with the above hypothesis is the report that tumour proliferative activity was associated with tumour angiogenesis in oesophageal squamous cell cancer (Nomiya et al , 2004; Li et al , 2008). …”
supporting
confidence: 84%
“…Also, Elpek et al (2001) have reported that CD34+-positive intra-tumoural microvessel density was associated with poorer survival in oesophageal squamous cell cancer. Finally, consistent with the above hypothesis is the report that tumour proliferative activity was associated with tumour angiogenesis in oesophageal squamous cell cancer (Nomiya et al , 2004; Li et al , 2008). …”
supporting
confidence: 84%
“…Previously, a significantly increased HDC‐positive microvessels density was shown in ESCC as compared with normal controls. Most of these HDC‐positive cells were CD34‐positive endothelial cells in microvessels with an increased proliferative capacity, suggesting that non‐mast cell histamine produced in endothelial cells might play a role in regulating angiogenesis in ESCC (Li et al ., 2008). Recently, the expression of H 4 receptors was demonstrated in ESCC, which was closely associated with clinicopathological features, including histological grade, primary tumour size, lymph node metastasis and patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…HDC is found in almost all mammalian tissues including the CNS6 and fetal liver,7 and HDC expression is increased in tumorigenic sites 8 9. After release, histamine is stored or degraded by histamine-N-methyltransferase and monoamine oxidase B (MAO-B) 5.…”
Section: Introductionmentioning
confidence: 99%